If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(z + 3) + 5 = 5z + 11 Reorder the terms: -4(3 + z) + 5 = 5z + 11 (3 * -4 + z * -4) + 5 = 5z + 11 (-12 + -4z) + 5 = 5z + 11 Reorder the terms: -12 + 5 + -4z = 5z + 11 Combine like terms: -12 + 5 = -7 -7 + -4z = 5z + 11 Reorder the terms: -7 + -4z = 11 + 5z Solving -7 + -4z = 11 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. -7 + -4z + -5z = 11 + 5z + -5z Combine like terms: -4z + -5z = -9z -7 + -9z = 11 + 5z + -5z Combine like terms: 5z + -5z = 0 -7 + -9z = 11 + 0 -7 + -9z = 11 Add '7' to each side of the equation. -7 + 7 + -9z = 11 + 7 Combine like terms: -7 + 7 = 0 0 + -9z = 11 + 7 -9z = 11 + 7 Combine like terms: 11 + 7 = 18 -9z = 18 Divide each side by '-9'. z = -2 Simplifying z = -2
| 3=c/d | | 7x+7=5y+140 | | y+12x=4 | | w/12.8=8 | | 99=8-4x+13 | | 3w=-6.3 | | 10x+7-3x=74 | | 3.5=8-x | | 2(f-2)=-16 | | 10(s-10)=-195 | | 2w=8.4 | | k-4.1=-9.38 | | -(c-10)=0 | | -2y-10=-3y+4+8y | | 18x=22+10x | | (3x-7)(2x+4)=0 | | 27/64 | | 2w-4=-12 | | y=ln(6x+5) | | -12/5x-5 | | 12-x=6x | | 6-5e^3x=30 | | (-5w-8)(7w-8)=0 | | 4.50x=4x+30 | | -7-8(5n-5)= | | (7x^2-2x^3)=((x-6)(x+6))+2x^2 | | (8x+2)(5x-10)=0 | | 15x-8x+7=-24 | | 2cos^26x-1=0 | | 2h-5=0.5(2) | | 6-5e^3x+1=30 | | (7x^2-2x^3)=((x*6)(x*6))+2x^2 |